Persistência na performance de fundos de investimento imobiliário brasileiros entre 2008 e 2012 - Guimarães, José Gustavo Macedo (2013)
The goal of this study is to evaluate the persistence in performance of real estate investment funds. In order to do that a methodology similar to Carhart (1997) was adopted: portfolios were select accordingly to the fund returns and performance was analyzed over time. Subsequently performance was evaluated through multifactor models. These models were created using indexes based on information from the Brazilian stock market and the IBOVESPA. The results indicate that high past returns real estate investment funds present persistence in their performance. In the case of multifactor models, it is concluded that the data used from the stock market do not mimic these funds. However, when modeling is performed using the IFIX a positive alpha exists for the high profit funds.